Effect of HIV Self-Testing on PrEP Adherence Among Gender-Diverse Sex Workers in Uganda: A Randomized Trial. (1st April 2022) - Mujugira, Andrew; Nakyanzi, Agnes; Nabaggala, Maria S.; Muwonge, Timothy R.; Ssebuliba, Timothy; Bagaya, Monica; Nampewo, Olivia; Sapiri, Oliver; Nyanzi, Kikulwe R.; Bambia, Felix; Nsubuga, Rogers; Serwadda, David M.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: HIV self-testing (HIVST) and pre-exposure prophylaxis (PrEP) are complementary tools that could empower sex workers to control their HIV protection, but few studies have jointly evaluated PrEP and HIVST in any setting. Methods: The Empower Study was an open-label randomized trial in Uganda. Sex workers were offered F/tenofovir disoproxil fumarate and randomized 1:1 to monthly HIVST and quarterly in-clinic testing (intervention) or quarterly in-clinic HIV testing alone (standard of care) and followed up for 12 months. PrEP adherence was measured using electronic adherence monitoring and tenofovir diphosphate (TFV-DP) levels in dried blood spots. Adherence outcomes and sexual behaviors were compared by arm using generalized estimating equation models. Results: We enrolled 110 sex workers: 84 cisgender women, 14 transgender women, 10 men who have sex with men, and 2 transgender men. The median age was 23 years. The 12-month retention was 75%. Nearly all (99.4%) used ≥1 HIVST kit. The proportion with TFV-DP levels ≥700 fmol/punch in the HIVST and standard of care arms at the 3-, 6-, 9-, and 12-month visits was 2.4%, 2.3%, 0%, and 0% and 7.9%, 0%, 0%, and 0%, respectively, with no differences by randomization arm ( P > 0.2). Self-reported condomless sex acts with paying partners was similar by arm [adjusted incidence rate ratio 0.70; 95% confidence interval (CI): 0.42 to 1.17; P = 0.18]. One seroconversion occurred (HIV incidence, 0.9/100 person-years); TFV-DP was not detected at any visit. Conclusions: A gender-diverse sample of sex workers in Uganda used HIVST but not daily oral PrEP for HIV protection. Alternate approaches to promote PrEP use, including long-acting formulations, should be considered in this population.